Mapping the superficial inferior epigastric system and its connection to the deep system: An MRA analysis. Issue 2 (February 2016) - Kurlander, David E.; Brown, Matthew S.; Iglesias, Rodrigo A.; Gulani, Vikas; Soltanian, Hooman T.
Summary: The superficial inferior epigastric vasculature plays a critical role in free abdominal tissue transfer. However, its anatomic variations are incompletely characterized. An investigation was conducted on the preoperative imaging of patients undergoing free-flap breast reconstruction by a single surgeon between 2008 and 2013. This study included patients who underwent abdominal magnetic resonance angiogram (MRA). A coordinate system was used to draw the main trunk and primary branches from each patient's superficial inferior epigastric system. Each hemiabdomen's branching pattern was categorized as simple, complex, or absent. The number of superficial-to-deep inferior epigastric connections and the presence or absence of a superficial system crossing the midline were recorded. Interrater reliability was assessed for two raters. This analysis included 53 patients (106 hemiabdomens). A total of 80 (75%) hemiabdomens were categorized as having simple and 10 (9%) as complex branching patterns. A total of 16 (15%) hemiabdomens had no identifiable vessels. At least one superficial-to-deep connection was found among 89 hemiabdomens (84%). Superficial systems crossing the midline were found in 14 patients (26%). Our findings support the high degree of anatomic variation in the superficial inferior epigastric system, including a significant number of patients lacking superficial-to-deep connections and bilaterally communicating systems. These variations may be identified on preoperative MRA.